2020
DOI: 10.1021/acsmacrolett.0c00434
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of Block Copolymer-Based Supramolecules in Solution

Abstract: Hierarchical assemblies from block copolymer (BCP)-based supramolecules have shown immense potential as programmable materials owing to ease to incorporate functional molecules and to access array of hierarchical structures. However, there remains a knowledge gap on the formation of the supramolecule in solution. Here, we applied NMR techniques to investigate the solution phase behavior of the most studied supramolecular systems, polystyrene-block-poly(4vinyl pyridine)(3-pentadecylphenol) (PS-b-P4VP(PDP) r ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Recent NMR studies confirmed the attachment of PDP to the 4VP in the supramolecule, thus the use of coil-comb shaped BCP reflects experimental condition. 33 The effect of intermolecular interactions on the nanoparticle ordering was examined using the interaction parameters listed in Table S2. When the pair interactions are representative of the experimental conditions, i.e., the interaction parameters of small molecules/coil block and small molecules/comb block are smaller than that of coil block/comb block, the nanoparticles spontaneously order into experimentally observed assemblies: nanoparticles span across both microdomains, the small molecules are concentrated near the nanoparticles, and the small molecules are present in both microdomains (Figure 2G,H).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent NMR studies confirmed the attachment of PDP to the 4VP in the supramolecule, thus the use of coil-comb shaped BCP reflects experimental condition. 33 The effect of intermolecular interactions on the nanoparticle ordering was examined using the interaction parameters listed in Table S2. When the pair interactions are representative of the experimental conditions, i.e., the interaction parameters of small molecules/coil block and small molecules/comb block are smaller than that of coil block/comb block, the nanoparticles spontaneously order into experimentally observed assemblies: nanoparticles span across both microdomains, the small molecules are concentrated near the nanoparticles, and the small molecules are present in both microdomains (Figure 2G,H).…”
Section: Resultsmentioning
confidence: 93%
“…A 4-component system was used containing a BCP with coil-comb structure to mimic the supramolecules, small molecules, and nanoparticles. Recent NMR studies confirmed the attachment of PDPs to the P4VP sidechains in the supramolecule, thus the use of coil-comb shaped BCP reflects experimental condition (29). The effect of intermolecular interactions on the nanoparticle ordering was examined using the interaction parameters listed in Table S3.…”
mentioning
confidence: 99%
“…The supramolecule consists of polystyrene- block -poly­(4-vinylpyridine), PS- b -P4VP, and 3-pentadecylphenol, PDP, at a molar ratio of 1.7:1 with the pyridine groups. The majority of the PDP occupies the pyridine sites in solution via hydrogen bonding while the remaining excess acts as a plasticizer that facilitates self-assembly. , PS­(19 000 Da)-P4VP­(5200 Da)­(PDP) 1.7 (lateral periodicity, L = 30 nm) was selected as the self-assembling matrix owing to its extensive structural diversity where morphological control of NPs ranging from 5 to 25 nm has been demonstrated. − , Iron oxide NPs were used as nonconductive nanofillers to leverage their absorption at wavelengths below 560 nm to facilitate the formation of thermal gratings used for TTG measurements . Furthermore, these particles have been incorporated into block copolymer matrices to fabricate superparamagnetic thin films .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The majority of the PDP occupies the pyridine sites in solution via hydrogen bonding while the remaining excess acts as a plasticizer that facilitates self-assembly. 26,27 PS(19 000 Da)-P4VP(5200 Da)(PDP) 1.7 (lateral periodicity, L = 30 nm) 22 was selected as the selfassembling matrix owing to its extensive structural diversity where morphological control of NPs ranging from 5 to 25 nm has been demonstrated. [23][24][25]28 Iron oxide NPs were used as nonconductive nanofillers to leverage their absorption at wavelengths below 560 nm to facilitate the formation of thermal gratings used for TTG measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DOSY is an NMR method [14][15][16][17] that reports diffusion coefficients (D) for individual resonances in NMR spectra. DOSY and the related pulsed field gradient (PFG) NMR diffusometry have been used to determine the M w and molecular weight distribution of synthetic polymers [15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and to characterize mixtures of polymers [35][36][37] and block copolymers [33,[38][39][40][41][42][43]. A useful tutorial on DOSY experiments for polymers was recently published [44].…”
Section: Introductionmentioning
confidence: 99%